2018
DOI: 10.1017/aer.2018.103
|View full text |Cite
|
Sign up to set email alerts
|

Heat alleviation studies on hypersonic re-entry vehicles

Abstract: A numerical simulation has been carried out to investigate the effects of leading edge blowing upon heat alleviation on the surface of hypersonic vehicles. The initial phase of this work deals with the ability of the present CFD-based techniques to solve hypersonic flow field past blunt-nosed vehicles at hypersonic speeds. Towards this end, the authors selected three re-entry vehicles with published flow field data against which the present computed results could be measured. With increasing confidence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(19 reference statements)
1
0
0
Order By: Relevance
“…In the extrapolation case, the conditions at the boundary are approximated to be the same value as one point off this boundary using zero differential. It should be noted that consistent with our earlier studies [28] on complex hypersonic configurations, the y + value for the meshes used in the present investigation was kept very close to 1. Dedicated grid convergence studies (results not shown for brevity) were carried out to assure that the final grid selected provided the most accurate and best converged solution.…”
Section: International Journal Of Aerospace Engineeringsupporting
confidence: 85%
“…In the extrapolation case, the conditions at the boundary are approximated to be the same value as one point off this boundary using zero differential. It should be noted that consistent with our earlier studies [28] on complex hypersonic configurations, the y + value for the meshes used in the present investigation was kept very close to 1. Dedicated grid convergence studies (results not shown for brevity) were carried out to assure that the final grid selected provided the most accurate and best converged solution.…”
Section: International Journal Of Aerospace Engineeringsupporting
confidence: 85%